REVERSE ENGINEERING OF SINGLE CYLINDER 600 CC LISTER DIESEL ENGINE WITH PURE PLANT OIL AS FUEL. CASE STUDY: CONNECTING ROD AND PISTON DESIGN - MARIO VALENTINO YASIN (NIM : 13107015); Dosen Pembimbing : Ir. Ignatius Pulung Nurprasetio, MSME
This final project is part of a research project on reverse engineering of a single cylinder 600 cc lister diesel engine. The research is a collaboration of three research groups within the Faculty of Mechanical and Aerospace Engineering (FMAE), namely Energy Conversion, Mechanical Production Engineering, and Mechanical Design. The focus of this final project is on the computer aided drafting (CAD) modeling as well as static and dynamic structural analysis. As a case study, we select the connecting rod and the piston. The reverse engineering activity starts by dismantling an imported lister diesel engine from India. All components are measured either by laser scanning, coordinate measuring machine (CMM), or manual measurement. The results are compiled and transformed into CAD data, which will become an input for the static and dynamic analysis. Stress analyses are performed by the bundled ANSYS finite-element software available in Autodesk Inventor. Load data are taken from the maximum torque specification of the engine, which are combined with computer simulation to determine the configuration of the maximum torque. For static analysis, the maximum combined stress is compared to the yield strength of the material, and for dynamic analysis, the maximum and minimum stresses at the most critical point are processed and plotted using the modified-Goodman diagram. Based on the analyses, the stresses are well beyond the yield strength, and the components under investigation are safe from fatigue failure. The above facts show that the lister diesel engine was designed using a very conservative approach. Therefore, there is ample room to modify the sizing of the connecting rod and the piston.